Analisis Semiotika dalam Video Animasi Berjudul “I am from Palestine” karya Rifk Ebeid - aisha nurdin; Aat Ruchiat Nugraha (Program Studi Ilmu Komunikasi Universitas Paramadina, 2026)
The Palestinian issue has been widely discussed since October 2023, when the event known as Thufan Al Aqsa took place. Various media are used to share information, raise awareness, and advocate for justice regarding the genocide, including Instagram's